(untitled) (Journal of the College of Basic Education, 2022)
The aim of the current research is to identify the effect of an educational program according to the Hermann model in the scientific fourth students’ learning of scientific thinking, and to verify the goal of the research, the researchers put a zero hypothesis stating that: There is no statistically significant difference at the level of significance (α = 0.05) between the mean scores The students of the experimental group who study according to a program prepared according to the Hermann model and the average scores of the students of the control group who study according to the usual method in the scientific thinking test